Case Study : Arrouha Sports & Outdoors / Nur Amirah Yusop - Yusop, Nur Amirah (2020)
Arrouha sports & outdoors a company that produces handmade bow in Malaysia. They sell handmade bow, arrow and accessories used for sport of archery that suits local people. I use SWOT method to help in resolve the problem and identify the problem with the solution that can made by the company it self. The major problem faced by Arrouha sports & outdoors are lacking of machine used and manpower. The company should hire more workers to help the production of products. In addition, they should introduce new machine to help the production workers produce product faster and more easily. Other than that the company should hire more workers to make sure they met the orders for their products